Pengaruh Penekanan Anggaran Terhadap Kinerja Manajerial Dengan Locus of Control Sebagai Variabel Moderasi di Universitas Widyatama - Paryati, Retno; Prameswari, Gitta; Christina M.P.P, Veronica (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to analyze the influence of budget emphasis in managerial performancewith locus of control as moderating variabele at Widyatama University. The methodused in this study was the explanatory survey. The population taken for this researchis the managers of Widyatama University which responsible for using the budget. Thenumber of questionnaires distributed in this study were 69 copies and thequestionnaires were returned by 55 copies. The study used Statical Package for SocialSciences (SPSS) ver. 20.0 to process the data. The empirical result of this researchindicate that budget emphasis has positive effect in managerial performance. Thesubsequent test find that locus of control has positive effect on managerial performanceas well, and moderation interaction positive on managerial performance. That means,locus of control can stengthen the relationships between budget emphasis andmanagerial performance